Mobile Messenger rating, sharing and engagement in global social commerce - Tan, Kiat Yao *; Teh, Phoey Lee *; Lee, Cheng Ean Catherine * (2015)
The use of the Short Message Service (SMS), available on mobile phones and other devices, for exchanging text messages is gradually diminishing. SMS has been replaced by Smart Phone Apps offering free messaging services; example include Whatsapp, Kakao, WeChat and Viber. The use of these platforms is constantly evolving; they are now used for advertising, group chatting, the sharing of information, and e-commerce communication. This paper provides a review of the currently available Mobile Messenger Applications, comparing their abilities, function and features. In particular the paper focuses on the engaging of these Apps in Global Social Commerce. In addition, the engagement of users towards sharing, commenting and rating the products and services were also discussed.